CC&C Garment{u2019}s new target customers and digital Platform - Phatutip Tongtun; Levermore, Roger; Badir, Yuosre F. M.; Ransom, Lakeesha K.; Royal Thai Government; Asian Institute of Technology Fellowships (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
This intern project was a collaboration between the school of management, Wecosystem and CC&C garment. The objective of this intern project is to let the student learn and work on real-life business problems. CC&C Garment is a garment factory with 300 employee producing shirts, hoodies, T-shirts with operation capacity of 100,000 pcs/month. This project objective is to solve 2 problems of CC&C Garment which are the lack of diverse customer and a purely offline contact channel. The solution of this project is working toward identifying and analyzing new target customer and creating a digital platform which includes market trends analysis, new target customer interview and analysis, CC&C Garment positioning, website key success factors and features, customer journey on the website, website mockup and website development options. In conclusion, this project proposed CC&C to look into smaller customer like young entrepreneur and fresh graduate. CC&C Garment could offer a one stop service, open to small order, be flexible and build a learning community. Lastly, CC&C Garment could build an online store and web application to provide the customer convenience and tools.
An Intern Project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Intern Project (M.B.A.) - Asian Institute of Technology, 2020
Keywords: Clothing trade -- Marketing